COMPARISON OF METHANE OXIDATION POTENTIAL BETWEEN COMPOST AND BLACK SOIL AT JERAM LANDFILL - Boon, Tien L.; P., Agamuthu (Malaysian Journal of Science, 2011)
Landfills are significant sources of atmospheric methane (CH4) that contributes to greenhouse gas effect, and therefore there is a need to reduce the CH4 emissions from landfills. Small scale landfills in Malaysia and other developing countries generally do not generate enough CH4 for energy harvest. CH4 emission can be reduced by means of microbial oxidation enhanced by biologically engineered landfill covers. This is a promising cost-effective technology to enhance biological oxidation of CH4 in small scale landfills. The selection of suitable materials represents one of the key issues in constructing biotic CH4 oxidation systems. Composts and black soil have been proven to support CH4 oxidation and they represent a low cost alternative to other sandy or humic-rich soil substrate. This study was carried out to investigate the CH4 oxidizing capacity of compost and black soil under field conditions. Experiments with different flow rates of landfill gas have shown that compost has a higher oxidation capacity compared to black soil. At 100 cm of cover height and flow rate of 300 ml per minute, black soil has an oxidation capacity of 112.2 ml CH4 per minute. For compost, the oxidation capacity is 169.8 ml of CH4 per minute. From this study we concluded that compost has greater potential than black soil as landfill cover material due to the better CH4 oxidation capacity.